(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2023)
It is acknowledged that access to high-quality water is crucial for any significant human development. Ten boreholes were used in obtaining the water sample. The samples were analyzed using the American Public Health Association (APHA) suggested procedures. The test parameters were compared to the chemical drinking water quality guideline established by the World Health Organisation. In a situation where the value is not provided, we relied on other pieces of literature. The research shows that the alkalinity, iron (Fe+), calcium (Ca2+), magnesium (Mg+), nitrate (NO3-), pH, conductivity, phosphate (PO43-), and total hardness (CaCO3) are all in line with the guidelines permissible limit which means are within the no-problem zone limits for health. While copper (Cu2+) was found to be within the permissible limit 2 mg/L in all the samples but BH1 (Junior Staff Quarters) 3mg/L which has health problems such as digestive disturbances, problems with the central nervous system, mucosal irritability, Wilson’s illnesses, and liver and kidney damage.